Efficacy of a Novel Granulocyte Monocyte Apheresis Adsorber Device in the Treatment of Inflammatory Bowel Diseases: A Pilot Study. Issue 6 (5th December 2016) - Di Girolamo, Maria; Sartini, Alessandro; Critelli, Rosina; Bertani, Angela; Merighi, Alberto; Villa, Erica
Abstract: Granulocyte monocyte apheresis (GMA) is a non‐pharmacological treatment for inflammatory bowel disease. In our study, we tested a novel GMA adsorber device in terms of clinical efficacy and safety in patients' non‐response to pharmacological therapy. Secondary outcomes were the evaluation of adsorber's technical performance, the reduction of inflammatory markers and the improvement of patients' life quality. The prospective study included 18 patients enrolled from 2011 to 2012 with a monitoring of 48 weeks. All patients with Crohn's disease achieved a clinical remission after GMA treatments, sustained until the end of follow up, while 80% of ulcerative colitis patients obtained a clinical benefit, maintained after 48 weeks of monitoring. Leukocytes, neutrophils, monocytes and platelets, compared to erythrocytes and lymphocytes, were effectively removed from peripheral blood. There was no statistically significant result about serological markers of inflammation. A consistent improvement of the patients' quality of life was observed up to the end of follow up. No significant side‐effects were recorded. Our study underlines the efficacy and the safety of this novel GMA adsorber device; a prospective randomized clinical trial with adequate sample size should be performed.